2022
DOI: 10.1177/09540083221114752
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, electrical and mechanical properties of carbon fiber/copper powder/carbon black reinforced hybrid Polyamide 6,6 composites

Abstract: The development of low electrical and thermal properties of Polyamide (PA), which is used in place of metals in engineering applications, draws attention to the developments in various industrial disciplines. In this study, the effects of metal and carbon based fillers on the properties of Polyamide 6,6 (PA 6,6) were investigated. Especially, copper powder (Cu), carbon black (CB), carbon fiber (CF) and hybrid fillers (Cu/CB/CF) reinforced composites based on PA 6,6 were prepared by twin-screw extruder followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Parameswaranpillai et al [ 43 ] have also found that the IS of PP/PS composite slightly reduced with the addition of CNTs, because CNTs cannot transfer stresses between PS dispersed phase and PP matrix. In another research, Beyaz et al [ 44 ] observed that the IS of PA 6.6/Cu composites decreased as the amount of copper powder increased, because a weak interaction was formed between the matrix and the filling material.…”
Section: Resultsmentioning
confidence: 99%
“…Parameswaranpillai et al [ 43 ] have also found that the IS of PP/PS composite slightly reduced with the addition of CNTs, because CNTs cannot transfer stresses between PS dispersed phase and PP matrix. In another research, Beyaz et al [ 44 ] observed that the IS of PA 6.6/Cu composites decreased as the amount of copper powder increased, because a weak interaction was formed between the matrix and the filling material.…”
Section: Resultsmentioning
confidence: 99%
“…In another study characteristic investigation of graphene nanoplates (GNP) filled polyamide nanocomposites is reported. The reduction in tan delta and increment in thermal stability of nanocomposites was seen [12]. There are several inorganic fillers reported in literature that when added to polymers enhanced their electrical, mechanical, and thermal properties.…”
Section: Introductionmentioning
confidence: 94%